SIKAP DAN PENILAIAN PRESTASI KERJA DARI PERSPEKTIF KARYAWAN DAN PIMPINAN PADA PT. BANK RIAU KEPRI CABANG BENGKALIS - Irma Darrini; Supriati Supriati; Muhammad Hamidi (Inovbiz: Jurnal Inovasi Bisnis, 2015)
Abstract:The Attitude is how the individual understand, experienced, reacted, and act toward and object, while work performance appraisal is evaluate the performance of employees according from the quality or the quantity standard that employees done. The purpose of this research are to know the attitude and work performance appraisal from employees perspective and to know the attitude and work performance appraisal from leadership perspective in PT. Bank Riau Kepri, Branch of Bengkalis. The Method use in this research was a comparative. The sampling technique in this research was used non probability sampling with 32 respodents. This research used primary data were collected using a questionnaire and interview. The results showed that from employees perspective the attitude categorized as very high with total score 4,30, that is mean employees assume that the attitude shown during work is very good. While for work performance appraisal categorized as high with total score4,14, that is mean employees assume that the performance shown during work is good. From leadership perspective the attitude that employees shown shown to the leadership, co-worker, and customer is consider good, and employeesperformance is also good and in accordance with the target set. Keywords: Attitude, Work Performance appraisal